ASYMMETRIC-SYNTHESIS OF (2S,3R)-3-AMINO-2-HYDROXYDECANOIC ACID - THE UNKNOWN AMINO-ACID COMPONENT OF MICROGININ - Bunnage, M; Burke, A; Davies, S; Goodwin, C (1994)
3-Amino-2-hydroxydecanoic acid (AHDA) is an unusual amino acid purported to occur in the recently isolated angiotensin-converting enzyme inhibitor microgipin. In order to elucidate the stereochemistry of the naturally occurring material, and thus complete the structural assignment of microginin, both the (2R,3R)-anti-diastereoisomer and the (2S,3R)syn-diastereoisomer of AHDA have been prepared. Comparison of the 1H and 13C nmr spectroscopic data of the synthetic amino acids with that reported for the naturally occurring material indicates that the relative stereochemisuy of the AHDA found in microginin is syn. The absolute stereochemistry of the natural amino acid is shown to be (2S,3R) by comparison of its reported CD spectrum with that recorded for the synthetic material prepared herein. © 1994.